Masa Depan Industri Kelapa Sawit Tantangan dan Peluang - Alpin Cristi Sitepu; Marzuti Isra; Alvi Ismu Azhar Panjaitan; Muhammad Rangga Juniarta; Novianur Safitri; Umar Bakri Hasibuan; Veny Wina Lestari Harahap (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
The Indonesian palm oil industry plays a strategic role as a major supporter of the national economy through its contribution to Gross Domestic Product (GDP), job creation, and rural infrastructure development. This article discusses in depth three main aspects: the economic benefits provided by the palm oil industry; challenges that include environmental issues, land conflicts, climate change, and regulation and productivity; and opportunities such as bioenergy development, diversification of derivative products, and utilization of technology and degraded land. The analysis also covers the role of technological innovation and human resource investment as key to the sustainability of this industry amidst global price fluctuations and international pressures on sustainability. With a data-driven approach and scientific literature review, this article highlights the importance of systemic transformation in the management of the palm oil industry to ensure competitiveness, environmental sustainability, and the welfare of local communities in the future.